2015
DOI: 10.1097/nne.0000000000000170
|View full text |Cite
|
Sign up to set email alerts
|

Introducing Information Literacy Competency Standards for Nursing

Abstract: The Association for College and Research Libraries published the Information Literacy Competency Standards for Nursing (ILCSN) in January 2014, written by a task force of the Health Sciences Interest Group of the American Library Association. The ILCSN describes skills ranging from basic to advanced information research competencies for students enrolled in nursing programs at all levels and for professional nurses. This article guides administrators and faculty in use of the standards to design programs and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 2 publications
0
10
0
Order By: Relevance
“…In two studies librarians were introduced to teach students information literacy [74, 77]. Librarians are experts in this field and are able to teach students the skills essential to EBP [74]. Librarians can support students in establishing and managing effective search techniques and help with reviewing and critiquing the information found.…”
Section: Discussionmentioning
confidence: 99%
“…In two studies librarians were introduced to teach students information literacy [74, 77]. Librarians are experts in this field and are able to teach students the skills essential to EBP [74]. Librarians can support students in establishing and managing effective search techniques and help with reviewing and critiquing the information found.…”
Section: Discussionmentioning
confidence: 99%
“…The survey questions were developed partly based on the author’s own experience teaching EBP to nurses as well as a review of the literature about EBP competencies for nurses [ 5 , 6 ] and the experience of health sciences librarians in teaching EBP to nurses and other health care professionals [ 8 , 10 , 13 , 19 , 20 ]. A face validity review of the survey instrument was conducted with the assistance of another health sciences librarian who also teaches EBP prior to the survey being sent to the MLA member list.…”
Section: Methodsmentioning
confidence: 99%
“…To identify the best available clinical evidence, nurses and other clinicians need to be competent in conducting literature searches and critically appraising evidence from research studies. Many nurses are uncomfortable with searching for research evidence in the literature [ 3 , 4 ], even though doing so has been identified as one of several competencies for nurses [ 5 , 6 ]. Based on their assessment of nurses’ perceived value of and ability to implement EBP, Hain and Haras concluded that professional nursing organizations could have a role in promoting EBP [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Of the 59 articles selected for inclusion in this review, 37.3% (n=22) used the terms related to nursing or nursing education in the article title directly, or they were published in a nursing or nursing education journal. This could be a reflection of Phelps, Hyde and Planchon Wolf (2015), who proposed that a relationship between librarians and faculty is required to ensure information literacy standards in nursing are met in nursing education and that nursing, as a profession, generally values the expertise of librarians (Phelps, Hyde & Planchon Wolf, 2015).…”
Section: 1mentioning
confidence: 99%